2001
DOI: 10.1038/labinvest.3780370
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Naturally Occurring E2F-4 Alterations on Transcriptional Activation and Proliferation in Transfected Cells

Abstract: SUMMARY:E2F is a family of transcription factors implicated in the regulation of gene expression required for progression through the G 1 -S transition. We have previously detected tumor-specific mutations at a trinucleotide repeat coding sequence of E2F-4 gene in a subset of human sporadic colorectal cancers. The purpose of this study was to investigate the potential functional consequences of these E2F-4 mutations. We transfected NIH3T3 fibroblasts with expression constructs containing wild-type as well as m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 19 publications
(20 reference statements)
1
7
0
Order By: Relevance
“…They demonstrated that the subcellular location of E2F‐4 was regulated in a cell cycle‐dependent manner. Takashima et al 23 also reported expression of E2F‐4 in both nuclei and cytoplasm. In contrast, Mady et al 20 found that E2F‐4 protein expression was strictly nuclear in position in normal and neoplastic colorectal tissues using the same antibody that we have utilized in this study.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…They demonstrated that the subcellular location of E2F‐4 was regulated in a cell cycle‐dependent manner. Takashima et al 23 also reported expression of E2F‐4 in both nuclei and cytoplasm. In contrast, Mady et al 20 found that E2F‐4 protein expression was strictly nuclear in position in normal and neoplastic colorectal tissues using the same antibody that we have utilized in this study.…”
Section: Discussionmentioning
confidence: 93%
“…Breast carcinoma cells showed a nuclear and/or granular cytoplasmic staining pattern (Figure 1). Because the subcellular localization of E2F‐4 is related to its functional state and its role in the cell cycle and cell growth 23, we assessed cytoplasmic and nuclear staining separately. Only staining of the invasive portion of the tumours was considered.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, E2F4 gene possesses a serine repeat trinucleotide (ACG) n , which is frequently mutated in various tumors including human sporadic colorectal cancers (29). These E2F4 mutations cause elevated transactivation of E2F consensus promoter sites and confer a growth advantage in rodent fibroblasts and HEK293 cells (74). It remains unknown, however, whether these genetic alterations affect E2F4 function in normal human intestinal crypt cells, especially with regard to the regulation of cell proliferation vs. cell survival.…”
Section: Discussionmentioning
confidence: 99%
“…The more frequent mutations observed are the deletion or the addition of a trinucleotide AGC and the deletion of 7 trinucleotides (Yoshitaka et al, 1996;Souza et al, 1997;Ikeda et al, 1998;Moriyama et al, 2002). Furthermore, Takashima et al, 2001, studied the impact of E2F4 mutations and observed an increase in nuclear expression, in transcriptional activity as well as in proliferation rate of fibroblasts overexpressing these mutants.…”
Section: Colorectal Cancermentioning
confidence: 99%